Association between Plasma Procalcitonin with Onset of MACE, in Patients with Acute ST elevated MI: An Unicentric Prospective Observational Comparative Study - Hassan, Md Mehedi; Safiuddin, Mohammad; Renu, Rafikun Nahar; Ahmed, Sharmin; Rahman, Sheikh Nashfiqur; Kulsum, Umme; Zaman, Md Hasan; Hasan, Md Nazmul; Rana, Masud; Mohammed, Noor; Proma, Sangita Banik; Anwar, AFM Azim (University Heart Journal, 2025)
Background: Cardiovascular diseases (CVDs) pose a significant global health threat, with South Asia, including Bangladesh, experiencing a substantial burden. Procalcitonin (PCT), a marker associated with bacterial infections and inflammatory responses, has been studied for its potential correlation with acute myocardial infarction (AMI). However, its role in predicting major adverse cardiac and cerebrovascular events (MACCE) in ST-segment elevation myocardial infarction (STEMI) remains underexplored in the Bangladeshi population. Methodology: This prospective observational study, conducted at the Department of Cardiology, BSMMU, aimed to investigate the prognostic significance of PCT in 54 STEMI patients within a one-month follow-up period. Enrollment criteria included admission within 12 hours of symptom onset. PCT levels were measured using chemiluminescence immunoassay (CLIA) technology. Comprehensive demographic, clinical, and diagnostic data were collected, and statistical analyses were performed, including univariate and multivariate logistic regression. Results: The study observed a significant association between high admission PCT levels and MACCE. In the high PCT group, 7 out of 27 patients experienced MACCE, compared to 3 out of 27 in the low PCT group (p = 0.038). Univariate and multivariate logistic regression analyses revealed elevated PCT as an independent predictor of MACCE (OR: 4.541, 95% CI: 2.119–6.521; AOR: 3.475, 95% CI: 1.962–5.546). Discussion: This study establishes the predictive role of procalcitonin in MACCE following STEMI. Elevated PCT levels on admission independently correlate with a heightened MACCE risk, showcasing its potential as a prognostic biomarker. The study’s observed MACCE rate of 18.5% within 30 days aligns with regional data, emphasizing the challenges in timely revascularization procedures. Correlations with Troponin and Creactive protein emphasize the inflammatory response’s role in adverse outcomes, contributing valuable insights for risk stratification in STEMI patients. Conclusion: This study contributes valuable insights into the prognostic significance of elevated PCT levels in predicting MACCE in STEMI patients. The independent association between high admission PCT and adverse outcomes suggests its potential as a prognostic biomarker. These findings emphasize the importance of PCT in risk stratification and decision-making for STEMI management in the Bangladeshi population. University Heart Journal 2024; 20(2): 67-71